2016
DOI: 10.1039/c5ew00186b
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating organic contaminant removal in an ozone-based water reuse process at full scale

Abstract: The 350 ML per d Eastern Treatment Plant (ETP) tertiary facility produces “Class A” water for the city of Melbourne, Australia, which is used for irrigation, dual reticulation and fire fighting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Estrone, triclosan, and carbamazepine were consistently present in the STMWRF filtered effluent and were mitigated/removed to below detection limit after ozonation. All three compounds are known to have high reactivities with ozone and/or hydroxyl radicals (Blackbeard et al, ). Caffeine was detected during one of the three sampling events and was oxidized during ozonation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Estrone, triclosan, and carbamazepine were consistently present in the STMWRF filtered effluent and were mitigated/removed to below detection limit after ozonation. All three compounds are known to have high reactivities with ozone and/or hydroxyl radicals (Blackbeard et al, ). Caffeine was detected during one of the three sampling events and was oxidized during ozonation.…”
Section: Resultsmentioning
confidence: 99%
“…TCEP is a flame retardant, it resists oxidation by design. TCEP is expected to be and is found to be resistive to ozone and hydroxyl radical oxidation (Blackbeard et al, ). Study results confirmed this expectation and work by others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These substances have not been encountered in any design process of traditional water and wastewater treatment plants. As Blackbeard et al (2016) observed, there were 91 MP compounds consistently presented in the secondary-treated effluent from Eastern Treatment Plant (Australia). In another survey carried out by Thomaidi et al (2015) in Greece, about 207 organic MPs were detected in different WWTPs, ranging from 1 ng/L to thousands ng/L.…”
Section: Introductionmentioning
confidence: 90%